Synchronization of decentralized event-triggered uncertain switched neural networks with two additive time-varying delays - Vadivel, Rajarathinam; Syed Ali, M.; Alzahrani, Faris; Cao, Jinde; Joo, Young Hoon (Nonlinear Analysis: Modelling and Control, 2020)
This paper addresses the problem of synchronization for decentralized event-triggered uncertain switched neural networks with two additive time-varying delays. A decentralized eventtriggered scheme is employed to determine the time instants of communication from the sensors to the central controller based on narrow possible information only. In addition, a class of switched neural networks is analyzed based on the Lyapunov–Krasovskii functional method and a combined linear matrix inequality (LMI) technique and average dwell time approach. Some sufficient conditions are derived to guarantee the exponential stability of neural networks under consideration in the presence of admissible parametric uncertainties. Numerical examples are provided to illustrate the effectiveness of the obtained results.
Keywords: event-triggered scheme; switched neural networks; Lyapunov–Krasovskii functional; exponential stability; average dwell time